1999
DOI: 10.1038/sj.ejhg.5200258
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype–genotype correlation in 20 deletion and 20 non-deletion Angelman syndrome patients

Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder caused by the absence of a maternal contribution to chromosome 15q11-q13. There are four classes of AS according to molecular or cytogenetic status: maternal microdeletion of 15q11-q13 (approximately 70% of AS patients); uniparental disomy (UPD); defects in a putative imprinting centre (IM); the fourth includes 20-30% of AS individuals with biparental inheritance and a normal pattern of allelic methylation in 15q11-q13. Mutations of UBE3A have recently be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
76
2
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 49 publications
11
76
2
2
Order By: Relevance
“…In a study describing the phenotypical differences in AS patients of different molecular classes, Bürger et al 8 pointed out that microcephaly and hypopigmentation are less frequently observed in patients with imprinting mutations than in patients with deletions. Similar findings have been reported by Moncla et al 5 Our study confirms these aspects. 5,8,18 All patients described by us had a normal head circumference for their age and normal pigmentation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In a study describing the phenotypical differences in AS patients of different molecular classes, Bürger et al 8 pointed out that microcephaly and hypopigmentation are less frequently observed in patients with imprinting mutations than in patients with deletions. Similar findings have been reported by Moncla et al 5 Our study confirms these aspects. 5,8,18 All patients described by us had a normal head circumference for their age and normal pigmentation.…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings have been reported by Moncla et al 5 Our study confirms these aspects. 5,8,18 All patients described by us had a normal head circumference for their age and normal pigmentation. In addition, they had normal or larger birth sizes, and all but one lacked epilepsy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Deletion defects give rise to a more severe phenotype with earlier onset, refractory epilepsy, more profound motor and neurodevelopmental delay, and poorer speech and language than those with uniparental disomy, imprinting or lone UBE3A mutation Angelman syndrome. The greater severity may be due to the associated loss of genes encoding GABA A subunits [16][17][18][19][20], which is not a feature of non-deletion Angelman syndrome. It is not known if this poses any additional hazards for anaesthesia.…”
Section: Discussionmentioning
confidence: 99%